Men With Hijab: Menetapkan Kejamakan Identitas Gender CrossHjaber di Media Sosial - Aly Mecca; Ahmad Fahrul Muchtar Affandi; Gumilar Pratama (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
Rejection of cross-hijaber is typical of societies with traditional genderideologies in Indonesia. In Indonesia, cross-hijaber is stigmatized withcriminal, psychiatric, and sexual disorders, as well as identity crises. Thisstudy examines how cross-hijaber displays his identity in the public andprivate spheres via social media, both communally and individually. Crosshijaber social identity and cross-hijaber personal identity are examined ingreater detail in this study. Using a virtual ethnographic method, the studyexamined cross-hijaber on a Facebook group. The results of the study revealthe diversity and complexity of cross-hijaber identities in social mediainteractions. The distinction between social and personal identities is nolonger distinct because the two can exchange positions depending on context.When cross-hijabers begin to wear their hijab, their cisgender identities willbe concealed. Even cross-hijaber identity is fluid based on the social context.Otherwise, when they become cisgender, the cross-hijaber identity will not bedisplayed.